PENGARUH PERAN IBU TERHADAP PEMBERIAN MP-ASI YANG TEPAT PADA BAYI USIA 6–12 BULAN: LITERATURE REVIEW - Milawati Ramli, Ramlah; Wulansari, Meinita; Sugarni, Mika; Wulandari, Bety Anisa; Rohmawati, Wahidah (Jurnal Multidisipliner Bharasumba, 2025)
Infancy, particularly between the ages of 6 and 12 months, is a critical period in growth and development that requires balanced nutrition. Breast milk remains the primary source of nutrition, but at this age, infants also need complementary foods. The quality of appropriate complementary feeding is influenced by the role of the mother as the primary caregiver, particularly in terms of knowledge, attitudes, skills, and feeding practices. A suboptimal role of the mother can lead to nutritional problems, stunting, and delayed growth and development. Objective: This study aims to review the influence of the mother's role on appropriate complementary feeding in infants aged 6–12 months through a literature review. Methods: This study used a literature review design. Articles were searched through the Google Scholar, PubMed, and ScienceDirect databases with a publication range of 2019–2024 using the keywords ‘mother's role’, ‘complementary feeding’, ‘infant feeding’, and ‘6–12 months’. Of the 52 articles found, 10 articles met the inclusion criteria and were analysed narratively based on their thematic suitability, methodology, and relevance to the research topic. Results: The literature analysis showed that the role of mothers greatly influenced the appropriateness of complementary feeding. Mothers' knowledge and positive attitudes are closely related to the choice of food types, frequency of feeding, and the amount of nutritional intake for infants. In addition, health education, nutritional counselling, and family support have been shown to improve mothers' ability to implement complementary feeding practices in accordance with WHO recommendations. Conclusion: The role of mothers is a key factor in the successful provision of appropriate complementary feeding for infants aged 6–12 months. Nutrition education, improved health literacy, and social support are crucial for optimising mothers' practices, thereby ensuring optimal infant growth and development.